2019
DOI: 10.1016/j.nicl.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal vascularization patterns: A high-resolution 7 Tesla time-of-flight magnetic resonance angiography study

Abstract: Considerable evidence suggests a close relationship between vascular and degenerative pathology in the human hippocampus. Due to the intrinsic fragility of its vascular network, the hippocampus appears less able to cope with hypoperfusion and anoxia than other cortical areas. Although hippocampal blood supply is generally provided by the collateral branches of the posterior cerebral artery (PCA) and the anterior choroidal artery (AChA), different vascularization patterns have been detected postmortem. To date,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 44 publications
5
56
0
Order By: Relevance
“…The brain neuroinflammation induced by peripheral nerve injury may be initiated at and distributed along the blood vessels. Our observation that the increase in PVMs and gliosis were most obvious in the hippocampus may simply be due to abundant blood vessels around the hippocampal fissure vulnerable to pathological challenges 34 , 35 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The brain neuroinflammation induced by peripheral nerve injury may be initiated at and distributed along the blood vessels. Our observation that the increase in PVMs and gliosis were most obvious in the hippocampus may simply be due to abundant blood vessels around the hippocampal fissure vulnerable to pathological challenges 34 , 35 .…”
Section: Discussionmentioning
confidence: 68%
“…To test if the increase in PVMs induced by SNI might interrupt BBB, we i.v. injected Evans blue or NaFlu and examined the hippocampus as there are abundant blood vessels around hippocampal fissure vulnerable to pathological challenges 34 , 35 . We found that BBB permeability was not disrupted by SNI ( Figure S5 A, B).…”
Section: Resultsmentioning
confidence: 99%
“…7T MRI allows for high‐resolution imaging of both the arteries [18,20] (time of flight) and the veins [19,21] (T2* weighted imaging/susceptibility weighted imaging). Postprocessing techniques are being developed for quantitative measures of vessel density, length, tortuosity, and branching patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that the p -values of right PCA PI were 0.058 and 0.084, which are more related to the degree of H-EPVS than MCA values. It may be because the origin of hippocampal arteries is the PCA or PCA branches, but further study with large population is needed ( 38 ).…”
Section: Discussionmentioning
confidence: 99%